Human Rights Due Diligence (HRDD) and Human Rights Impact Assessment (HRIA) Best Practices to Corporate Shared Value (CSV): A Case of British Petroleum Tangguh Project In Papua - Carolina Martha; Jerry Marcellinus Logahan (Bina Nusantara University, 2016)
The Tangguh Liquefied Natural Gas (LNG) Project is a planned natural gas development project located in the remote area of Berau-Bintuni Bay in Papua Province, Indonesia. British Petroleum (BP) Tangguh project aims tobe the pioneer in producing natural gas. It can be concluded that BP contributes an innovative approach, bearing in mind to sustainable development, cultural preservation and biodiversity conservation. Therefore, in each of its corporate actions, BP always integrates the value of community, partnership, consultation and corporate responsibility. It is mentioned that through experience and observation, BP as an extractive company, haveestimated the costs of not finding a better mechanism to adjust to social challenges can be higher than the costs of the uncertainties inherent in the trial of new ideas. However, according to international Non-GovernmentalOrganization (NGO), Down to Earth, BP has conducted a series of human rights violations by exploiting natural resources in Papua and restricting Papuans in enjoying their fundamental human rights. If only the BP keeps this Tangguh project in line with its aim to accommodate concerns from the affected surroundings, thus, will surely bring positive changes in BP’s corporate shared value.